Elden eller evigheten? - Reinius, Lotten Gustafsson (Tidsskrift for kulturforskning, 2008)
This article concerns collections, acquired by Swedes in the Congo State (1885-1908), and housed today at the Ethnographic Museum in Stockholm and the Museum of World Culture in Gothenburg. Museum items are approached in this article, not primarily as tokens of Congolese material culture, but as traces of cultural history involving Swedes as much as Congolese, and as points of entry to a critical museology. Drawing on case studies of collections created by men and women with differing roles in the colonial process, I discuss the ways in which artefacts have been selected, joined and charged with new functions and meanings in collections and museums of ethnography. My points of departure are a selected amount of objects that, analytically, have worked as what Roland Barthes (1980) calls punctum: the detail that disturbs and fascinates by force of seeming ungrammatical in relation to the larger context of which it forms part. Examining objects by hand, has allowed for an interpretive process inspired by all senses. By referring to the exemplified punctums as material, I want to stress the analytical and critical benefits to be gained by working with (virtually untouchable) museum items as multisensory phenomena.